Death is now my neighbour - Dexter, Colin, 1930-2017 (Inspector Morse, 1996)
The peaceful quadrangle of Lonsdale College seems remote from the shocks of the outside world - such as the shooting of a young woman in her North Oxford home.But things at Lonsdale are not as tranquil as they appear.The Master of the college is retiring, and two senior dons, Denis Cornford and Julian Storrs, are vying, discreetly but furiously, to succeed him.There are only two people to whom the coveted appointment means more than it does to Cornford and Storrs - their wives.Chief Inspector Morse, investigating the murder on Bloxham Drive, follows a trail that leads first to a tabloid journalist, then to the strip clubs of Soho.It soon winds back, however, to the university.For Morse and his partner, Sergeant Lewis, the question becomes:Is the Mastership of Lonsdale worth killing for?